2020
DOI: 10.3390/cancers12113414
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Risk According to Regimens for Eradication of Hepatitis C Virus; Interferon or Direct Acting Antivirals

Abstract: By pegylated interferon (PegIFN)-free direct-acting antivirals (DAAs) against hepatitis C virus (HCV) infection, a sustained virological response (SVR) rate >95% can be attained with a satisfactory tolerability and shorter treatment duration. However, it remains controversial whether there is any difference in prognosis depending on regimens—PegIFN or DAAs. We compared the probabilities of hepatocellular carcinoma (HCC) development between patients achieving an SVR by PegIFN/ribavirin (PegIFN group, n = 603… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Individuals with a high BMI (≥ 25.0 kg/m 2 ) accompanied by low triglyceride levels (< 160 mg/dL) had a significantly increased risk for liver cancer related mortality[ 276 ]. In the DAA era, increase in HCC incidence after treatment has been associated with higher BMI and cirrhosis[ 277 ]. A systematic review demonstrated a significant association between BMI and HCC risk.…”
Section: Hcv and Metabolic Syndromementioning
confidence: 99%
“…Individuals with a high BMI (≥ 25.0 kg/m 2 ) accompanied by low triglyceride levels (< 160 mg/dL) had a significantly increased risk for liver cancer related mortality[ 276 ]. In the DAA era, increase in HCC incidence after treatment has been associated with higher BMI and cirrhosis[ 277 ]. A systematic review demonstrated a significant association between BMI and HCC risk.…”
Section: Hcv and Metabolic Syndromementioning
confidence: 99%
“…Several therapeutic strategies have been developed to eliminate HCV infection. Among these, direct-acting antivirals (DAAs) represent a major breakthrough in viral eradication [50][51][52]. However, these therapies do not eliminate the virus-induced HCC risk, especially in patients with liver cirrhosis [53,54].…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…It remains unclear whether there is a difference in risk for hepatocarcinogenesis based on different treatment regimens (IFN or DAA), considering the potential effect of DAAs on angiogenesis and cellular proliferation. 6,7 Challenging clinical questions associated with HCC patients who have achieved an SVR include, why HCC develops and what differences exist between patients who develop HCC after an SVR and those who do not. HCV-induced epigenetic changes associated with hepatocarcinogenesis were found to persist after an SVR in clinical samples 8 and after virus eradication in cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of patients at a high risk for developing HCC would improve prognosis and reduce unnecessary medical costs. It remains unclear whether there is a difference in risk for hepatocarcinogenesis based on different treatment regimens (IFN or DAA), considering the potential effect of DAAs on angiogenesis and cellular proliferation 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation